Analytical prediction of flexural behaviour of RC slabs strengthened with non-prestressed and prestressed CFRP strips - Dushimimana, Aloys (2023)
The flexural behaviour of reinforced concrete (RC) slabs strengthened with carbon fibre reinforced polymer (CFRP) laminates is analytically addressed in this work. Analytical approaches are developed for (i) near-surface mounted (NSM), (ii) externally bonded reinforcement (EBR), and the EBR prestressed using (iii) mechanical anchorage (MA) and (iv) gradient anchorage (GA) systems. The analytical results show a good agreement with those from experimental program. Besides, the performance of two existing formulae for predicting the mid-span deflection is assessed, and the performance of the recent fib Bulletin 90 technical report for predicting the ultimate capacity of the strengthened RC slabs is appraised.